qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Number of solution
Answer
circle-check-icon
expand-arrow-icon
Relationship between roots and coefficients
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = 2 x ^ { 2 } - 2 x + 5$
$y = 0$
$y$Intercept
$\left ( 0 , 5 \right )$
Minimum
$\left ( \dfrac { 1 } { 2 } , \dfrac { 9 } { 2 } \right )$
Standard form
$y = 2 \left ( x - \dfrac { 1 } { 2 } \right ) ^ { 2 } + \dfrac { 9 } { 2 }$
$2x ^{ 2 } -2x+5 = 0$
$\begin{array} {l} x = \dfrac { 1 + 3 i } { 2 } \\ x = \dfrac { 1 - 3 i } { 2 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 }$
$ $ Divide both sides by the coefficient of the leading highest term $ $
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 2 } } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 2 } } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - \dfrac { 1 } { 2 } \right ) ^ { 2 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
$ $ Move the constant to the right side and change the sign $ $
$\left ( x - \dfrac { 1 } { 2 } \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x - \dfrac { 1 } { 2 } \right ) ^ { 2 } = - \dfrac { 5 } { 2 } + \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$ $ When raising a fraction to the power, raise the numerator and denominator each to the power $ $
$\left ( x - \dfrac { 1 } { 2 } \right ) ^ { 2 } = - \dfrac { 5 } { 2 } + \dfrac { \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 ^ { 2 } } { 2 ^ { 2 } } }$
$ $ Organize the expression $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 9 } { 4 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 9 } { 4 } }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 9 } { 4 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 9 } { 4 } } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 3 i } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 3 i } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 i } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 i } { 2 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 i } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 i } { 2 } } \end{array}$
$ $ Organize the expression $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 + 3 i } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 - 3 i } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { 1 + 3 i } { 2 } \\ x = \dfrac { 1 - 3 i } { 2 } \end{array}$
Calculate using the quodratic formula$($Imaginary root solution$)
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 }$
$ $ Solve the quadratic equation $ ax^{2}+bx+c=0 $ using the quadratic formula $ \dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - \left ( - 2 \right ) \pm \sqrt{ \left ( - 2 \right ) ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 } }$
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 2 \right ) \pm \sqrt{ \left ( - 2 \right ) ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$ $ Simplify Minus $ $
$x = \dfrac { 2 \pm \sqrt{ \left ( - 2 \right ) ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$x = \dfrac { 2 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$x = \dfrac { 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm \sqrt{ - 36 } } { 2 \times 2 } }$
$x = \dfrac { 2 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 36 } } } { 2 \times 2 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { 2 \pm \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 1 } } } { 2 \times 2 }$
$x = \dfrac { 2 \pm 2 \times 3 \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 1 } } } { 2 \times 2 }$
$ $ It is $ \sqrt{-1} = i$
$x = \dfrac { 2 \pm 2 \times 3 \color{#FF6800}{ i } } { 2 \times 2 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm 2 \times 3 i } { 2 \times 2 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm 6 i } { 4 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm 6 i } { 4 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 + 6 i } { 4 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 - 6 i } { 4 } } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 2 + 6 i } { 4 } } \\ x = \dfrac { 2 - 6 i } { 4 } \end{array}$
$ $ Reduce the fraction $ $
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 1 + 3 i } { 2 } } \\ x = \dfrac { 2 - 6 i } { 4 } \end{array}$
$\begin{array} {l} x = \dfrac { 1 + 3 i } { 2 } \\ x = \color{#FF6800}{ \dfrac { 2 - 6 i } { 4 } } \end{array}$
$ $ Reduce the fraction $ $
$\begin{array} {l} x = \dfrac { 1 + 3 i } { 2 } \\ x = \color{#FF6800}{ \dfrac { 1 - 3 i } { 2 } } \end{array}$
$ $ Do not have the solution $ $
Calculate using the quadratic formula
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 2 \right ) \pm \sqrt{ \left ( - 2 \right ) ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$ $ Simplify Minus $ $
$x = \dfrac { 2 \pm \sqrt{ \left ( - 2 \right ) ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$x = \dfrac { 2 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$x = \dfrac { 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$x = \dfrac { 2 \pm \sqrt{ \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$ $ Calculate power $ $
$x = \dfrac { 2 \pm \sqrt{ \color{#FF6800}{ 4 } - 4 \times 2 \times 5 } } { 2 \times 2 }$
$x = \dfrac { 2 \pm \sqrt{ 4 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } } } { 2 \times 2 }$
$ $ Multiply the numbers $ $
$x = \dfrac { 2 \pm \sqrt{ 4 \color{#FF6800}{ - } \color{#FF6800}{ 40 } } } { 2 \times 2 }$
$x = \dfrac { 2 \pm \sqrt{ \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 40 } } } { 2 \times 2 }$
$ $ Subtract $ 40 $ from $ 4$
$x = \dfrac { 2 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 36 } } } { 2 \times 2 }$
$x = \dfrac { 2 \pm \sqrt{ - 36 } } { \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } }$
$ $ Multiply $ 2 $ and $ 2$
$x = \dfrac { 2 \pm \sqrt{ - 36 } } { \color{#FF6800}{ 4 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm \sqrt{ - 36 } } { 4 } }$
$ $ The square root of a negative number does not exist within the set of real numbers $ $
$ $ Do not have the solution $ $
$ $ Do not have the real root $ $
Find the number of solutions
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 }$
$ $ Determine the number of roots using discriminant, $ D=b^{2}-4ac $ from quadratic equation, $ ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 }$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 5$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$D = 2 ^ { 2 } - 4 \times 2 \times 5$
$D = \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 5$
$ $ Calculate power $ $
$D = \color{#FF6800}{ 4 } - 4 \times 2 \times 5$
$D = 4 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 }$
$ $ Multiply the numbers $ $
$D = 4 \color{#FF6800}{ - } \color{#FF6800}{ 40 }$
$D = \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 40 }$
$ $ Subtract $ 40 $ from $ 4$
$D = \color{#FF6800}{ - } \color{#FF6800}{ 36 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ - } \color{#FF6800}{ 36 }$
$ $ Since $ D<0 $ , there is no real root of the following quadratic equation $ $
$ $ Do not have the real root $ $
$\alpha + \beta = 1 , \alpha \beta = \dfrac { 5 } { 2 }$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 }$
$ $ In the quadratic equation $ ax^{2}+bx+c=0 $ , if the two roots are $ \alpha, \beta $ , then it is $ \alpha + \beta =-\dfrac{b}{a} $ , $ \alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 2 } { 2 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 5 } { 2 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 2 } { 2 } } , \alpha \beta = \dfrac { 5 } { 2 }$
$ $ Solve the sign of a fraction with a negative sign $ $
$\alpha + \beta = \color{#FF6800}{ \dfrac { 2 } { 2 } } , \alpha \beta = \dfrac { 5 } { 2 }$
$\alpha + \beta = \color{#FF6800}{ \dfrac { 2 } { 2 } } , \alpha \beta = \dfrac { 5 } { 2 }$
$ $ Reduce the fraction $ $
$\alpha + \beta = \color{#FF6800}{ 1 } , \alpha \beta = \dfrac { 5 } { 2 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo